Language, Education and Nation-building assimilation and shift in Southeast Asia - Sercombe, Peter G.; Tupas, T. Ruanni F. (Palgrave studies in minority languages and communities, 2014)
"This volume tracks the complex relationships between language, education and nation-building in Southeast Asia, focusing on how language policies have been used by states and governments as instruments of control, assimilation and empowerment. The individual chapters each represent one of the countries in the region, namely Brunei, Cambodia, East Timor, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand and Vietnam. Written by established and well-known scholars of language, education and politics in Southeast Asia, the chapters examine the place of minority or non-dominant languages in nation-building agendas and practices, as well as their impact both on the linguistic ecology of specific countries and on the cultural, socio-economic and political well-being of their speakers. With a recent worldwide push towards multilingual education as one way to address the cultural, political and economic marginalization of millions of people around the world, this volume also examines the possibilities and challenges of implementing mother tongue-based education programmes in the region".